Geoid versus quasigeoid: a case of physics versus geometry - VANÍČEK, Petr; KINGDON, Robert; SANTOS, Marcelo (Contributions to Geophysics and Geodesy, 2012)
For decades now the geodetic community has been split down the middle overthe question as to whether geoid or quasigeoid should be used as a reference surface forheights. The choice of the geoid implies that orthometric heights must be considered, thechoice of the quasigeoid implies the use of the so-called normal heights. The problem withthe geoid, a physically meaningful surface, is that it is sensitive to the density variationswithin the Earth. The problem with the quasigeoid, which is not a physically meaningfulsurface, is that it requires integration over the Earth’s surface.Density variations that must be known for the geoid computation are those withintopography and these are becoming known with an increasing accuracy. On the otherhand, the surface of the Earth is not a surface over which we can integrate. Artificial“remedies” to this fatal problem exist but the effect of these remedies on the accuracy ofquasigeoid are not known. We argue that using a specific technique, known as Stokes-Helmert’s and using the increased knowledge of topographical density, the accuracy ofthe geoid can now be considered to be at least as good as the accuracy of the quasigeoid.